Keterlibatan KKP-DR UIN Mataram pada masa pandemi Covid-19 dalam upaya mewujudkan kampung sehat di Desa Batutulis - Suparmanto Suparmanto; Tri Mulya Lestari (Jurnal Participative: Jurnal Pengabdian Pada Masyarakat, 2021)
Covid-19 is a disease caused by a new type of corona virus that first appeared in Wuhan, China at the end of 2019. Symptoms of Covid-19 are cough, fever, and shortness of breath. Covid-19 infection causes quite high mortality in various countries, including Indonesia. Covid-19 has also changed all aspect which has become a prolonged crisis mus immediately find a solution so that it does not have an even greater impact. One of the efforts made by the government to prevent the spread of the Corona-19 virus is by implementing restrictions on community activities that take place in regions in Indonesia. Another government institution that is also involved in minimizing the impact of Covid-19 is UIN Mataram. The involvement of UIN Mataram in this case is to direct its students to carry out Participatory Work From Home Lectures. The implementation of the Participatory Work From Home is focused on aspects of education and health. However, the priority is in the health aspect. In Batutulis Village, Jonggat, Central Lombok, various efforts were made by students on health aspect. Where this is in line with the goal of the Batutulis Village Head to create a healthy village. Healthy in this case is not only physically and spiritually healthy but also the environment in which it is occupied is also healthy. So the effort made are to carry out mutual cooperation in cleaning the environment such as ditches and rivers which are often used as garbage dumps, cleaning mosques, doing healthy exercise with the community and socializing the prevention of the spread of Covid-19.